Function Of Notary In The Appointment Of Extra-Marital Children As Testamento Heirs - Sari, Emala; Gozali, Djoni Sumardi; Hafidah, Noor (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
In inheritance law, it has been regulated regarding inheritance for extra-marital children differently in accordance with the principles regulated by civil inheritance law which certainly rests on justice. In a condition where an extra-marital child who does not get recognition, can get inheritance through testamentair or will. The granting of a will containing efrstelling in the form of an openbaar testament to an unrecognized extra-marital child is an effort to fulfill a sense of justice. Justice is basically a relative thing, which does not always have to be the same, something can be said to be fair if it has done something according to the appropriate provisions. As the concept of distributive justice put forward by Aristotle, namely justice that gives everyone a portion according to their achievements. This legal research method is normative legal research. The approaches in this research are statutory, and conceptual approaches. The results of this study state that wills containing efrsteling against unrecognized extra-marital children in the form of openbaar terstamen have provided a sense of justice. This is because the Openbaar testament to an unrecognized extra-marital child has fulfilled the provision of rights to all heirs including extra-marital children who get a share in the inheritance, in other words, the principle of justice has been fulfilled due to the openness of the testator made before a notary and in the presence of witnesses. The notary plays a role in providing legal counseling to the person who will make a testament on an extra-marital child. The granting of Openbaar Testamen to extra-marital children has fulfilled a sense of justice. This is because the Openbaar Testament is an open form of testament so that the child outside of marriage can know the part to which he is entitled.